Enhancing English communication skills and self-efficacy: A blended learning approach with digital storytelling in primary education - Lifei Peng; Jirarat Sitthiworachart (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to explore the impact of a blended learning approach incorporating digital storytelling on the English communication skills and self-efficacy of 80 sixth-grade students in China. Using a mixed-methods approach, two sixth-grade classes at Tongren Second Primary School were selected, with one class taught using the blended learning with digital storytelling method and the other receiving traditional instruction. Pre-tests and post-tests were administered to assess students' English communication skills and self-efficacy, with quantitative data analyzed using statistical methods and qualitative data gathered through in-depth interviews. Results showed that the experimental group demonstrated significantly higher self-efficacy (mean score of 122.83) and communication skills (mean score of 23.83) compared to the control group (mean scores of 89.65 and 17.43, respectively). The qualitative analysis revealed increased motivation, perceived improvement in communication skills, and enhanced self-efficacy among students. This study concludes that the blended learning approach with digital storytelling effectively enhances the English communication skills and self-efficacy of Chinese primary school students, offering a promising educational tool for modern teaching settings. The findings suggest practical implications for educators to integrate digital storytelling into the curriculum to create an engaging learning experience and boost students' confidence and motivation.
Keywords: Digital Storytelling and Education; Subtitles and Audiovisual Media; Literacy, Media, and Education